Model Project-Based Learning (PJBL) pada Pembelajaran Al-Islam di SMK Muhammadiyah 2 Kota Malang - Alya Dinia Asyfiqi Masykur; Romelah Romelah (Moral : Jurnal kajian Pendidikan Islam, 2025)
This study aims to describe how project-based morality material (Project-Based Learning/PjBL) is implemented at SMK Muhammadiyah 2 Malang City. This study uses a qualitative approach with a case study type of research. Data analysis uses the Miles, Huberman and Saldana data analysis test and data validity test using triangulation. Data collection techniques through observations carried out on implementation in the classroom, interviews with teachers and students, and documentation during learning. The results of the study show that through the project-based learning model by making videos about the morality of mahmudah and mazmumah, students gain their own experience, namely being able to design, determine, identify and solve problems in their groups.